Inclusion of diabetic retinopathy screening strategies in national-level diabetes care planning in low-income and middle-income settings: protocol for a scoping review. Issue 9 (18th September 2020) - Curran, Katie; Piyasena, Prabhath; Congdon, Nathan; Duke, Lisa; Malanda, Belma; Peto, Tunde
Abstract : Introduction: The diabetes mellitus (DM) epidemic is a major public health concern globally, with the highest-burden in low-income and middle-income countries (LMICs). Diabetic retinopathy (DR) is a microvascular complication of diabetes, and if left untreated can lead to visual impairment and blindness. Epidemiological studies suggest that the incidence of sight-threatening DR is decreasing in high-income countries due to improved treatments and management of DM; however, these trends are not replicated in LMICs. In this paper, we outline a scoping review protocol that aims to identify which LMICs have included DR in their national DM, non-communicable disease or prevention of blindness plans. The scoping review also aims to assess gaps when implementing national DR screening programmes in LMICs. Methods and analysis: This scoping review will follow the Arksey and O'Malley (2005) methodology and the Preferred Reporting Items for Systematic Review and Meta-Analysis extension for Scoping Review guidelines. A comprehensive search of peer-reviewed and grey literature will be conducted from October 1989 (St. Vincent Declaration) to February 2020. Studies will be identified from electronic databases; Medline, Embase and CENTRAL (Cochrane Library). To identify further relevant articles, a hand search will be conducted using the reference lists of included studies. Two reviewers will independently screen records for relevant data and disagreements about eligibility will be resolved through consensus or arbitration by a third reviewer. A quantitative analysis will be performed to highlight key findings and thematic analysis will be used to identify emerging themes and subthemes from included studies. The key themes will highlight countries progress in terms of national-level DR service planning and screening implementation. Ethics and dissemination: No ethical approval is required because the scoping review methodology aims to synthesise information from publicly available resources. The results will be disseminated through conference presentations and peer-reviewed publication.